Renaissance papers 2011 - Shifflett, Andrew Eric, 1964-; Gieskes, Edward, 1968- (Renaissance papers, 2012)
Beginning with three essays on Shakespeare: on '1 Henry 4', 'Love's Labour's Lost', and 'Titus Andronicus', this year's volume then turns to links between Renaissance drama and the wider culture, with essays on Marlowe's 'Massacre at Paris', experimental plays of the dawn of the seventeenth century, and 'Bartholomew Fair' and 'Othello'. Next come essays on a trio of lyric poets: Sir Philip Sidney, Fulke Greville, and George Herbert. Three final essays focus on topics in the history of ideas: Trinitarianism in Spenser, social satire and Christian exemplarity, and the censorship of Cardinal Bell.